The Enhancer of split and Achaete-Scute complexes of Drosophilids derived from simple ur-complexes preserved in mosquito and honeybee. - Schlatter, R.; Maier, D. (BMC Evolutionary Biology, 2005)
In Drosophila melanogaster the Enhancer of split-Complex [E(spl)-C] consists of seven highly related genes encoding basic helix-loop-helix (bHLH) repressors and intermingled, four genes that belong to the Bearded (Brd) family. Both gene classes are targets of the Notch signalling pathway. The Achaete-Scute-Complex [AS-C] comprises four genes encoding bHLH activators. The question arose how these complexes evolved with regard to gene number in the evolution of insects concentrating on Diptera and the Hymenoptera Apis mellifera.In Drosophilids both gene complexes are highly conserved, spanning roughly 40 million years of evolution. However, in species more diverged like Anopheles or Apis we find dramatic differences. Here, the E(spl)-C consists of one bHLH (mbeta) and one Brd family member (malpha) in a head to head arrangement. Interestingly in Apis but not in Anopheles, there are two more E(spl) bHLH like genes within 250 kb, which may reflect duplication events in the honeybee that occurred independently of that in Diptera. The AS-C may have arisen from a single sc/l'sc like gene which is well conserved in Apis and Anopheles and a second ase like gene that is highly diverged, however, located within 50 kb.E(spl)-C and AS-C presumably evolved by gene duplication to the nowadays complex composition in Drosophilids in order to govern the accurate expression patterns typical for these highly evolved insects. The ancestral ur-complexes, however, consisted most likely of just two genes: E(spl)-C contains one bHLH member of mbeta type and one Brd family member of malpha type and AS-C contains one sc/l'sc and a highly diverged ase like gene.